Targeting the PI3K/AKT/mTOR pathway in lung cancer: mechanisms and therapeutic targeting - Qiang, Min; Chen, Zhe; Liu, Hongyang; Dong, Junxue; Gong, Kejian; Zhang, Xinjun; Huo, Peng; Zhu, Jingjun; Shao, Yifeng; Ma, Jinazun; Zhang, Bowei; Liu, Wei; et al. (Frontiers in Pharmacology, 2025)
Owing to its high mortality rate, lung cancer (LC) remains the most common cancer worldwide, with the highest malignancy diagnosis rate. The phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling (PAM) pathway is a critical intracellular pathway involved in various cellular functions and regulates numerous cellular processes, including growth, survival, proliferation, metabolism, apoptosis, invasion, and angiogenesis. This review aims to highlight preclinical and clinical studies focusing on the PAM signaling pathway in LC and underscore the potential of natural products targeting it. Additionally, this review synthesizes the existing literature and discusses combination therapy and future directions for LC treatment while acknowledging the ongoing challenges in the field. Continuous development of novel therapeutic agents, technologies, and precision medicine offers an increasingly optimistic outlook for the treatment of LC.